LABOR BEHAVIOR IN EMPLOYEE EVALUATIONS OF A VERTICALLY INTEGRATED OIL COMPANY - Hajrullina, Nursafa; Konev, Vitaliy; Subbotin, Vladimir; Cherepanova, Vera; Bogdanova, Juliya (Revista Inclusiones, 2020)
The article is based on the results of a questionnaire survey conducted by scientists of the Industrial University of Tyumen in October 2019 as part of the implementation of the grant of the LUKOIL Charity Fund, the sample size is 177 people. The article examines the labor behavior of employees of a vertically integrated oil company using the example of four divisions of LUKOIL-West Siberia LLC. To identify the features of labor behavior, respondents’ responses were analyzed depending on their gender, age, education, work experience, and other indicators. Skillful use of the obtained data will allow managers of structural divisions to use the labor potential of subordinates more effectively and increase their return in the process of labor activity.